Developing an ELT supplementary student book on saprahan for cookery department - Isti Arbaniah; Regina Regina; Nining Ismiyani (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
The purpose of this research was to develop an ELT supplementary student book on Saprahan for Cookery Department in vocational schools. Saprahan is the local traditional method of serving the dish for guests.  Adopting a developmental method of research, ADDIE instructional design was employed as the phase in developing the materials.  The book is intended to be extensive reading material. From the need analysis, it can be concluded that both the teachers and students need the product. Not only the product can be used in Special Menu or Food and Beverage Service as its supposedly original use, but it may also function as an English subject at school. The result of the design phase showed that the product was designed in a Content-Based Instruction philosophy. Then, the development phase successfully resulted in the production of an ELT supplementary student book on Saprahan with six units explaining general description, procedure, equipment, menus, event, and news of Saprahan. The implementation phase showed that all students were interested in the book and 81% of the students agreed that the book would enhance their learning. Finally, the experts’ assessment in the evaluation phase showed that the product was feasible and effective for students in enriching their knowledge and skills.